Tourism Marketing Research Trends: Bibliometric Analysis Using Scopus Database - Awang, Mesak Yamres; Niha, Simon Sia; Rane, Melvin Krisdiana Djami (Jurnal Ilmiah Wahana Pendidikan, 2025)
With the increasing competition in the global tourism industry, an in-depth understanding of marketing research trends and developments is becoming increasingly important. This study reviews the development of international tourism marketing research over the past two decades (2002-2024) by analyzing 592 articles from the Scopus database. The aim is to identify trends, key themes, and key contributors in this field. Bibliometric analysis reveals a paradigm shift in tourism marketing strategies, with increasing emphasis on sustainability, personalization, and digital technologies. The results show a significant increase in research interest in this topic, with contributions from 332 authors from 66 countries. Publications are concentrated in prestigious journals such as Sustainability and Tourism Management. This study provides valuable insights for academics, practitioners, and policymakers in understanding the dynamics of tourism marketing research and formulating strategies that are relevant to current developments. The findings of this study suggest that customer-oriented, sustainable, and IT-enabled approaches will increasingly dominate the future of tourism marketing.